Balancing Costs and Care: Nonoperative Appendicitis Treatment Outcomes in Pakistan - Bilal Fattani; Umme Roman Akhtar; Khushboo Nusrat (Journal of the Pakistan Medical Association, 2024)
Dear Respected Editor, In Pakistan, approximately 110,000 cases of appendicitis are reported annually [1], highlighting the condition's prevalence and significance. Traditional management predominantly revolves around widely practiced surgical intervention, such as appendectomy. [2]. Immediate appendectomy has become the standard treatment due to the significant morbidity and mortality difference between perforated and non-perforated acute appendicitis. However, the country's healthcare landscape presents a complex challenge due to varying regional access to medical resources. This variation in healthcare infrastructure exacerbates the difficulty of effectively managing appendicitis and underscores the need for solutions that strike a balance between clinical outcomes and economic considerations. While appendectomy remains a standard surgical procedure, it comes with inherent disadvantages, chief among them being the cost burden it places on patients and healthcare systems [3]. For patients in a low- to middle-income nation like Pakistan, the financial strain associated with surgery—which includes preoperative evaluations, surgical costs, hospital stays, and postoperative care—can be challenging [4]. Furthermore, the ripple effects affect the whole healthcare system, diverting resources that may otherwise be used for other urgent medical needs. A study by Siddiqui et al. emphasizes the need for a comprehensive analysis of economic factors in appendicitis management, particularly in low- and middle-income countries like Pakistan. The challenges in countries such as Pakistan require the exploration of alternative approaches that can optimize clinical outcomes while effectively managing healthcare costs without compromising patient care. [2] The recent study by Lee et al. introduces a promising alternative to conventional appendicitis management [5]. The research focuses on nonoperative treatment approaches, such as antibiotic therapy and observation, which have gained traction for their potential benefits Further, the study shows that the majority of the patients who had nonoperative treatment did not encounter a recurrence of appendicitis and were able to avoid surgical intervention for a period of around 20 years. Furthermore, there is a lack of data indicating any long-term dangers associated with nonoperative care. One of the prominent advantages lies in the reduction of immediate healthcare expenses, which can alleviate the financial burden on both patients and healthcare systems. By presenting evidence on the effectiveness and safety of nonoperative approaches, this study opens avenues for a paradigm shift in appendicitis management in Pakistan. The potential to achieve comparable clinical outcomes while minimizing the economic burden is a compelling proposition that warrants further exploration and consideration within Pakistan's healthcare challenges.